irSynthesis and Study of AntitumorActivity of Substituted Imidazolecarboxamides: Antitumor activity of imidazolecarboxamides - Farzin Hadizadeha; Mohammad Ramezani; Zahra Tayarani; Maryam Eghbal (Iranian Journal of Pharmaceutical Sciences, 2007)
In view of potential biological activities of small molecule polyamides, wesynthesized some novel N-(2-aminoethyl)-1-benzyl-2- (alkylthio)-1H-imidazole-5-carboxamide (7a,b), and N-(2-(1-benzyl-2-(alkylthio) -1H-imidazole- 5-carboxamido)ethyl)-1-benzyl-2- (alkylthio)-1H-imidazole-5-carboxamides (8a,b) as antitumoragents. The antitumor activity of compounds 7a,band 8a,bwas studied atconcentrations of 0.01, 0.1 and 1 mg/ml, using the potato disk bioassay technique.Vincristine at 0.25 mg/ml employed as positive control and had -67.24% tumorinhibition. Maximum % inhibition for potato tumors was found to be -75.52 for 7bat 1 mg/ml.